Electrical Vehicle Power Line Communication - Tristan Daru , Alexander; Purnama, Irwan; Rusdinar, Angga (eProceedings of Engineering, 2025)
Abstract - Nowadays, electric vehicle is starting to be a reguler thing in a daily life, especially in advanced countries, while Indonesia is currently adopting that concepts. In an eletric vehicle, there is a Controlled Area Network (CAN) which functions as the central area for all the data distribution through out the vehicle, including sensors, part conditions, and others. Insaparable activity from electric vehicles is charging, since it is one of the most crucial factors to runs properly. Having a communication mechanism between the vehicle with the charging station would give benefits, for both the user also the vehicle, making it possible to have a direct diagnostic of the vehicle state while regulerly charging it. That is the main reason for a developmet in Electric Vehicle Power Line Communication (EVPLC). The goal is to assure that it is possible to have a data transfer activity with bidirectional communication mechanism through the running AC current that charges the battery of the vehicle. While grasping that concept, the researchers created an EVPLC module through a simulated Electrical Vehicle Charging Station (EVCS) and Electrical Vehicle Controlled Area Network (EVCAN) simulation to prove the concept to be implemneted onto a real EVCS and electric vehicle. Keywords - CAN, Bidirectional, EVCS, EVCAN, AC